Human Endogenous Retrovirus HERV-K14 Families: Status, Variants, Evolution, and Mobilization of Other Cellular Sequences - Flockerzi, Aline (American Society for Microbiology, 2005)
The human genome harbors many distinct families of human endogenous retroviruses (HERVs) that stem from exogenous retroviruses that infected the germ line millions of years ago. Many HERV families remain to be investigated. We report in the present study the detailed characterization of the HERV-K14I and HERV-K14CI families as they are represented in the human genome. Most of the 68 HERV-K14I and 23 HERV-K14CI proviruses are severely mutated, frequently displaying uniform deletions of retroviral genes and long terminal repeats (LTRs). Both HERV families entered the germ line ∼39 million years ago, as evidenced by homologous sequences in hominoids and Old World primates and calculation of evolutionary ages based on a molecular clock. Proviruses of both families were formed during a brief period. A majority of HERV-K14CI proviruses on the Y chromosome mimic a higher evolutionary age, showing that LTR-LTR divergence data can indicate false ages. Fully translatable consensus sequences encoding major retroviral proteins were generated. Most HERV-K14I loci lack an env gene and are structurally reminiscent of LTR retrotransposons. A minority of HERV-K14I variants display an env gene. HERV-K14I proviruses are associated with three distinct LTR families, while HERV-K14CI is associated with a single LTR family. Hybrid proviruses consisting of HERV-K14I and HERV-W sequences that appear to have produced provirus progeny in the genome were detected. Several HERV-K14I proviruses harbor TRPC6 mRNA portions, exemplifying mobilization of cellular transcripts by HERVs. Our analysis contributes essential information on two more HERV families and on the biology of HERV sequences in general.